Analysis of immiscible liquid-liquid mixing in stirred tanks by Electrical Resistance Tomography. (14th December 2020) - Maluta, Francesco; Montante, Giuseppina; Paglianti, Alessandro
Graphical abstract: Highlights: The liquid-liquid dispersion regime transitions are investigated. The ERT technique is used to identify liquid-liquid regimes objectively. Limits on the use of ERT and possible source of errors are identified. Radial and axial profiles of the light liquid volumetric fraction are determined. Abstract: In this work, the dispersion of diesel fuel in water in a baffled tank stirred by a Rushton turbine is investigated. The impeller speeds corresponding to the initial drawdown, the just dispersed regime and the completely dispersed regime are identified by suitable variables obtained by means of the Electrical Resistance Tomography technique. The effect of the dispersed phase volume fraction and of the impeller off-bottom clearance on the different dispersion regimes is considered. The impeller Froude number, the Archimedes number and a dimensionless distance between the liquid-liquid interface position and the impeller elevation are adopted for the data interpretation. For the investigated system, the local volume fraction profiles show that the completely dispersed condition is practically achieved above the just dispersed impeller speed, with negligible gradients of the local volume fraction distribution in the axial direction.